2020
DOI: 10.1016/j.yclnex.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single mega dose injection of vitamin D on serum adiponectin concentration at first gestational diabetes mellitus: A randomized controlled clinical trial

Abstract: Results: Serum 25 OH vitamin D increase significantly in the intervention but not in the control group from 24.25 to 62.10 (nmol/L) (p-value < 0.01). Comparison in within group showed that adiponectin level increased significantly only among intervention group after the vitamin D injection from 7.45 to 8.98 (ngr/ dL) (P-value ¼ 0.01), while between group comparisons showed no significant differences in adiponectin concentration after the intervention (P-value < 0.05). Between and within group comparisons repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Quite similar to the findings of the current study, another 2020 study from Iran revealed that a single intramuscular dose of VD3 injection (300,000 IU) was very much effective in not only improving the circulatory status of VD3 in mothers with GDM after delivery but it also significantly helped to boost the circulatory levels of adiponectin [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Quite similar to the findings of the current study, another 2020 study from Iran revealed that a single intramuscular dose of VD3 injection (300,000 IU) was very much effective in not only improving the circulatory status of VD3 in mothers with GDM after delivery but it also significantly helped to boost the circulatory levels of adiponectin [14].…”
Section: Discussionsupporting
confidence: 88%
“…VD receptors have been identified in almost every type of cell in the body, suggesting the potential role of VD3 in regulating various metabolic pathways. VD3 regulates the function of β-pancreatic cells and insulin sensitivity in different body tissues, and there is a 1.29-fold increase in the risk of GDM with every 5 ng/mL decrease in VD3 levels [ 14 ]. Hosseinzadeh et al reported that the levels of VD3 are negatively associated with body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen publications were evaluated by browsing the full studies in accordance with methods described in the literature, but some did not have sufficient data in the results. Finally, a total of 12 trials including 13 studies [9,10,[18][19][20][21][22][23][24][25][26][27] were eligible for full-text assessment. In the trial conducted by Dabbaghmanesh, we included two studies with Dongdong Li, Ningtao Fu, Hui Wu different interventions of vitamin D supplementation.…”
Section: Study Selection Processmentioning
confidence: 99%
“…122 Moreover, a single intramuscular injection of vitamin D (300,000 IU) can improve the adiponectin level in gestational diabetes mellitus. 123 Multiple studies have revealed that vitamin D is inversely correlated with the level of proinflammatory cytokines, such as TNFα, interleukin (IL) 1 beta (IL1β), IL6, IL8, IL17A and IL33 (Fig. 5b).…”
Section: Role Of Vitamin D In Hepatic Inflammationmentioning
confidence: 99%